Determinants of Personal Hygiene Behaviour of Adolescent During Menstruation in Junior High Schools in Jakarta - Trimawartinah, Trimawartinah; Azzahra, Hashifah Salma (Universitas Mandala Waluya, 2025)
Adolescent girls are prone to infections of the reproductive organs during menstruation, this can occur if they do not perform good menstrual hygiene. This study aims to determine the determinants of adolescent personal hygiene behaviour during menstruation at SMPN X Jakarta in 2024. This study used a cross-sectional design with stratified random sampling technique. The total population was 429 in all classes VII, VIII and IX, with a sample size of 94 who met the inclusion criteria. Data collection used a questionnaire instrument that was filled in directly by the respondent. Descriptive data analysis uses frequency counts and percentages, while relationship analysis with the chi-square test with a degree of significance of 5%. The results of the research data showed that more than half behaved well on personal hygiene during menstruation 79 students (84%), had high knowledge 72 students (76.6%), thought that Water, Hygiene and Sanitation (WASH) facilities were adequate during menstruation as many as 55 students (58.5%), and received peer support 62 students (66%). The results of the relationship test stated that there was a significant relationship between personal hygiene behaviour and the variables of knowledge (p value= 0.045) and peer support (p value= 0.044), but there was no significant relationship on the variable of school facilities related to water, hygiene, and sanitation (p value= 0.874). It is recommended that there should be a continuous health programme between increasing knowledge and increasing peer support, so that the problem of female reproductive organ hygiene can be resolved.